1983
DOI: 10.1080/00268978300101641
|View full text |Cite
|
Sign up to set email alerts
|

Excited state energetics of aniline-rare-gas van der Waals complexes

Abstract: Aniline-Nen and aniline-Arn (n = 1 and 2) complexes were synthesized in continuous and in pulsed supersonic expansions and interrogated by laserinduced fluorescence. Information on the formation kinetics and excited state energetics was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…The main fluorescence peak due to the n = 2 complex appears at -106 cm -~ from the free aniline transition, i.e. twice the n = I spectral shift, which confirms the equivalence of the sites occupied by the first two Argon atoms, above and below the plane of the Aniline ring, as already discussed by other authors [9,,Io]. However no other narrow feature which could be attributed to clusters with n > 3 can be observed in the fluorescence spectra.…”
Section: / Tsupporting
confidence: 80%
“…The main fluorescence peak due to the n = 2 complex appears at -106 cm -~ from the free aniline transition, i.e. twice the n = I spectral shift, which confirms the equivalence of the sites occupied by the first two Argon atoms, above and below the plane of the Aniline ring, as already discussed by other authors [9,,Io]. However no other narrow feature which could be attributed to clusters with n > 3 can be observed in the fluorescence spectra.…”
Section: / Tsupporting
confidence: 80%
“…Figure 3 shows the associated fluorescence excitation spectrum in the lowest energy spectral region. The polarizability (19) of CH, is 0.29 x lo-" cm3 which is greater than that of Ar and thus, based on the above discussion, dispersion interactions again appear to be the major source of the excited state stabilization. This is illus- Can 4.…”
Section: B Molecular Itzteractions Of Itzdole With Selected Halomethmentioning
confidence: 99%
“…to the red of the associated bare molecule transition). Amirav et al (19) have shown that for the aniline-Ar van der Waals system, the contribution of dipole -induced dipole interactions to the total excited spectral shift is approximately 5%. The simplest expression for this dipole -induced dipole stabilization energy using a point dipole approximation is given by (16), where p is the dipole moment of the polarizer (in this case indole) and a is the polarizability of the complexing partner in the van der Waals molecule.…”
Section: B Molecular Itzteractions Of Itzdole With Selected Halomethmentioning
confidence: 99%
“…Ar, were exhibited, revealing two spectral features; (3) the spectral features of the So + SIX transition are blue shifted, being located at Sv = + 8 ? 1 cm-I; (4) For personal use only. spectroscopic evidence for the existence of a single energetically stable structure of the H2P-Arl complex.…”
Section: Discussionmentioning
confidence: 99%